Use of Digital Health Interventions for Cancer Prevention Among People Living With Disabilities in the United States: A Scoping Review - Chinenye Lynette Ejezie; Lea Sacca; Sylvia Ayieko; Sara Burgoa; Yasmine Zerrouki; Diana Lobaina; Goodness Okwaraji; Christine Markham (Cancer Medicine)
ABSTRACT Background The use of digital health strategies for cancer care increased dramatically in the United States over the past 4 years. However, a dearth of knowledge remains about the use of digital health for cancer prevention for some populations with heath disparities. Therefore, the purpose of the present scoping review was to identify digital health interventions for cancer prevention designed for people with disabilities. Methods This scoping review was guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses extension for scoping reviews and the Arksey and O'Malley methodological framework. The Embase, PubMed, Ovid MEDLINE, and CINAHL/EBSCO databases were searched for peer‐reviewed articles published from database inception to February 5, 2024. Reports published in English of studies that employed digital health strategies for cancer prevention, were conducted among people with disabilities regardless of age, and were conducted in the United States were included. Findings Following screening for eligibility, seven articles were identified. The types of disabilities were cancer (n = 4), bipolar I or II disorder (n = 1), obesity (n = 1), and deafness (n = 1). Interventions focused on education (n = 4), screening (n = 3), smoking cessation (n = 3), physical activity (n = 1), and cessation support (n = 1). Digital health strategies consisted of educational content delivered online, text messaging, interactive educational games, and downloadable informational applications. The common outcome of interest across all manuscripts was intervention efficacy. Interpretation Overall, limited research is available to evaluate the use of digital health for cancer prevention among people with disabilities. This review identified gaps in knowledge that, if addressed, may help guide continued innovation in the use of digital health strategies for cancer prevention among people with disabilities.